IMPLEMENTASI PERATURAN WALIKOTA PADANG PANJANG NOMOR 37 TAHUN 2018 TENTANG TATA CARA PENGELOLAAN DAN PEMBERDAYAAN PASAR PUSAT DI KOTA PADANG PANJANG - Aulia Khairunisa Khairunisa; Adil Mubarak (Jurusan Ilmu Administrasi Negara, 2023)
This research aims to describe the implementation of Padang Panjang Mayor Regulation Number 37 of 2018 concerning Procedures for Management and Empowerment of the Central Market in Padang Panjang City. This research is motivated by the existence of regulations regarding the management of wholesale markets which were previously traditional markets with the aim of creating representative markets as a means of driving the regional economy. In this research, researchers used descriptive methods with a qualitative approach. To collect research data through observation, interviews and documentation studies. Testing the validity of the research data obtained using method triangulation and source triangulation techniques. In this research, problems were found regarding the management and empowerment of the central market of Padang Panjang City, where the mayor's regulations were still not fully complied with by traders selling, and there were even traders selling outside the applicable provisions and contracts. to this regulation. This problem will have an impact on the convenience of the buying and selling process between traders and potential buyers and will not properly organize the placement of traders which must be in accordance with the commodity/zoning. Research on procedures for managing and empowering the central market in Padang Panjang City adapts to the scope of procedures for managing and empowering the central market in Padang Panjang City which includes: 1) terms and procedures for placing traders, 2) rights and obligations of traders, 3) cooperation central market management, 4) control and evaluation, and 5) central market empowerment.